1967
DOI: 10.4141/cjps67-055
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Carbaryl on Two Apple Cultivars

Abstract: No elTect v'as noted on quality and kceping properties of the fruit, nol did carbaryl influence reducing-sugar and acid le'r.els, and acid-sugar ratio. Bean stem curvature tests indicated that the chemical interfered u'ith the transport system of the treated apple trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Since carbaryl at 0.02 per cent caused about the same degree of thinning as at 0.08 per cent it appears there is no necessity to use concentrations higher than 0.02 to 0.04 per cent for commercial thinning of Granny Smith in southern Victoria. This confirms the results of Batjer and Thomson 1961 ;Cripps and Halse 1962 ;Stebins 1962 ;Southwick, Weeks and Olanyk 1964 ;Teskey and Kung 1967, who found that carbaryl does not have any significant ability to increase the rate of thinning at higher concentrations. The fungicide thiram also caused significant thinning of Granny Smith apples similar to that obtained by carbaryl.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since carbaryl at 0.02 per cent caused about the same degree of thinning as at 0.08 per cent it appears there is no necessity to use concentrations higher than 0.02 to 0.04 per cent for commercial thinning of Granny Smith in southern Victoria. This confirms the results of Batjer and Thomson 1961 ;Cripps and Halse 1962 ;Stebins 1962 ;Southwick, Weeks and Olanyk 1964 ;Teskey and Kung 1967, who found that carbaryl does not have any significant ability to increase the rate of thinning at higher concentrations. The fungicide thiram also caused significant thinning of Granny Smith apples similar to that obtained by carbaryl.…”
Section: Discussionsupporting
confidence: 89%
“…Since then, this material has been widely tested and numerous authors (Batjer and Thomson 1961 ;Cripps and Halse 1962 ;Stebins 1962 ;Batjer and Billingsley I 964 ;Southwick, Weeks and Olanyk 1964 ;Teskey and Kung 1967 ;andVeinbrants 1961 and1963) found that carbaryl is a very effective and consistent thinning agent for certain apple varieties. In addition, thinning with this material does not increase with concentration (Batjer and Thomson 1961 ;Cripps and Halse 1962 ;Teskey and Kung 1967).…”
mentioning
confidence: 99%
“…The reduction in titratable acidity content in carbaryl treated samples was not significant, as in other cases. Teskey and Kung [32] reported that the carbaryl application in apple cultivation also did not influence the level of acids in apples. The crude protein content of azadirachtin, cypermethrin and carbaryl treated fruit samples was found to be nonsignificant in comparison to the control.…”
Section: Resultsmentioning
confidence: 99%
“…Carbaryl appears to thin by interfering with the movement of vital chemicals in the vascular tissue (Teskey and Kung 1967).…”
Section: Apples 79mentioning
confidence: 99%